2014
DOI: 10.1099/jmm.0.068247-0
|View full text |Cite
|
Sign up to set email alerts
|

Detection of enterovirus 68 as one of the commonest types of enterovirus found in patients with acute respiratory tract infection in China

Abstract: Human enterovirus 68 (HEV-68) is an enterovirus associated with respiratory illness. In China, no information about HEV-68 is available for children yet. This study aimed to investigate the presence of HEV-68 in mainland China between 2009 and 2012 and to explore the migration events of HEV-68 across the world. Among 1565 samples tested from children, 41 (2.6 %) were positive for HEV and 223 (14.3 %) for human rhinovirus (HRV). Seven (17.1 %) of 41 HEVs were HEV-68. Two HEV-68-and five HRV-positive samples wer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
49
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 52 publications
(50 citation statements)
references
References 19 publications
1
49
0
Order By: Relevance
“…Our phylogenetic analyses are notable in that they suggest a relatively complex molecular evolution of EV-D68 during the 2014 outbreak. Before this outbreak, EV-D68 was rarely reported and was associated with mild respiratory illness, although small outbreaks had been documented since 2005 (15,16,(18)(19)(20)(21)(22)(23)(24)(25)(26)(27)(28)(29)(30)(31)(32)(33). Previous studies showed that the A, B, and C clades circulated or cocirculated during different time periods in different geographic regions (15,16,18,19,(21)(22)(23)(24)(25)(26)(27)(28)(29)(30)(31)(32)59).…”
Section: Discussionmentioning
confidence: 99%
“…Our phylogenetic analyses are notable in that they suggest a relatively complex molecular evolution of EV-D68 during the 2014 outbreak. Before this outbreak, EV-D68 was rarely reported and was associated with mild respiratory illness, although small outbreaks had been documented since 2005 (15,16,(18)(19)(20)(21)(22)(23)(24)(25)(26)(27)(28)(29)(30)(31)(32)(33). Previous studies showed that the A, B, and C clades circulated or cocirculated during different time periods in different geographic regions (15,16,18,19,(21)(22)(23)(24)(25)(26)(27)(28)(29)(30)(31)(32)59).…”
Section: Discussionmentioning
confidence: 99%
“…Surveillance studies in Japan, China, and the Netherlands revealed that enterovirus D68 was responsible for less than 1% of acute viral respiratory infections and that the incidence of infection peaked between September and November. [3][4][5] In a US enterovirus surveillance report of cases between 1970 and 2005, enterovirus D68 was identified in only 26 of 49 637 cases. 6 A total of 68 cases of enterovirus D68 infection were reported among clusters of infection in Asia, Europe, and the United States between 2008 and 2010.…”
Section: Discussionmentioning
confidence: 99%
“…Following the initial outbreaks, EV-D68 continued its seasonal circulation, and was occasionally detected in respiratory samples from paediatric patients with URTI and severe LRTI in different countries, further supporting its clinical relevance [83][84][85][86]. Further concern was raised after the EV-D68 outbreak in the USA in 2014 [87], when over 1000 patients across the country were diagnosed with acute respiratory illness (ARI) caused by EV-D68.…”
Section: Enterovirus 68mentioning
confidence: 99%